Laminated glass and method for producing laminated glass

By using hardened transparent resin in the bonding part of the laminated glass and controlling the temperature and pressure during the manufacturing process, the color unevenness caused by the deformation of the light control members due to heat flow and pressure changes is solved, and the light transmission and absorption performance of the laminated glass is improved.

JP7661973B2Active Publication Date: 2025-04-15AGC INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022543910
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-21
Filing Date
2021-08-11
Publication Date
2025-04-15
Estimated Expiration
2041-08-11

AI Technical Summary

Technical Problem

During the high-temperature and high-pressure processing of existing laminated glasses, light control members are prone to deform due to changes in heat flow and pressure, resulting in uneven light transmission or absorption, and the problem of uneven color.

Method used

A laminated glass structure is adopted that includes a first glass plate, a second glass plate, a light shield member, an adhesive portion and a seal member, wherein the adhesive portion comprises a hardenable transparent resin and reduces deformation of the light-controlled member by controlling temperature and pressure during the manufacturing process.

Benefits of technology

It effectively reduces the deformation of light control members, reduces the occurrence of color unevenness, and improves the light transmission and absorption performance of laminated glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661973000002
    Figure 0007661973000002
  • Figure 0007661973000003
    Figure 0007661973000003
  • Figure 0007661973000004
    Figure 0007661973000004
Patent Text Reader

Abstract

Provided are: a laminated glass which rarely undergoes the unevenness in color of an optical member; and a method for manufacturing the laminated glass. This laminated glass comprises a first glass sheet, a second glass sheet which faces the first glass sheet, and a light control member to which an electric power supply body is connected, an adhesive part and a seal member which are arranged between the first glass sheet and the second glass sheet, in which the seal member overlaps with at least a portion of the periphery of the first glass sheet when observed in the plan view, the adhesive part comes into contact with the first glass sheet, the second glass sheet, and a first main surface, a second main surface and a side surface of the light control member, and the adhesive part contains a curable transparent resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated glass and a method for producing the laminated glass. [Background technology]

[0002] There are light-controlling materials that can adjust the light transmittance. For example, light-controlling materials that use suspended particles whose alignment state changes depending on whether an electric field is applied or not, polymer dispersed liquid crystal (PDLC), guest host liquid crystal (GHLC), etc. are known.

[0003] In recent years, it has been proposed to manufacture laminated glass in which such a light control member is sandwiched between glass plates (see, for example, Patent Document 1). Polyvinyl butyral (PVB) resins and ethylene-vinyl acetate copolymer (EVA) resins, which are called interlayer films, have been widely used to bond the glass plates together. A laminate containing the resin is treated at high temperature and high pressure in an autoclave or the like to sufficiently bond the glass plates together. In this case, the high temperature causes the interlayer film to flow so as to fit the gap between the glass plates. In addition, the high pressure causes the gap between the glass plates to change, and in some cases the glass plates are elastically deformed, resulting in a distribution in the amount of change in the gap. The light control member also deforms in accordance with these changes, and local discoloration (hereinafter also referred to as color unevenness) due to deviations in the thickness of the light control member may occur.

[0004] In addition, in light control components using liquid crystal, the liquid crystal tends to easily become unevenly distributed, as the liquid crystal attempts to mitigate the force (stress) applied to the light control element that deforms the element by flowing, which can result in problems with color unevenness. Color unevenness in light control components is undesirable because it impairs aesthetics and reduces light transmission / blocking performance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2016-164617 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in consideration of the above problems, and has an object to provide a laminated glass in which color unevenness in a light control member is reduced. [Means for solving the problem]

[0007] A laminated glass according to one embodiment of the disclosure comprises a first glass plate, a second glass plate facing the first glass plate, and a dimming member to which a power supply is connected, an adhesive portion, and a sealing member between the first and second glass plates, wherein the sealing member overlaps at least a portion of the periphery of the first glass plate in a plan view, the adhesive portion contacts the first glass plate, the second glass plate, and the first main surface, second main surface, and side surface of the dimming member, and the adhesive portion contains a curable transparent resin.

[0008] A manufacturing method for laminated glass according to one embodiment of the disclosure is a manufacturing method for laminated glass including a first glass plate, a second glass plate facing the first glass plate, and a light control member to which a power supply is connected, an adhesive portion, and a sealing member between the first glass plate and the second glass plate, the manufacturing method including: a forming step of forming the sealing member on at least a part of the periphery of at least one of the first glass plate and the second glass plate in a plan view, and forming an adhesive portion containing a curable transparent resin on at least one main surface of the first glass plate and the second glass plate; a laminating step of forming a laminate in which the first glass plate, the adhesive portion, and the second glass plate are laminated in this order, and the adhesive portion contacts the first glass plate, the second glass plate, and the first main surface, the second main surface, and a side surface of the light control member to which the power supply is connected; and a bonding step of joining the first glass plate, the adhesive portion, the second glass plate, and the sealing member to each other in the laminate. Effect of the Invention

[0009] According to one embodiment of the disclosure, it is possible to provide a laminated glass in which color unevenness in a light control member is reduced. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view of the laminated glass according to the first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of the laminated glass according to the first embodiment. [Diagram 3] 3(a) and 3(b) are a plan view and a cross-sectional view of the laminated glass according to the first embodiment. [Figure 4] FIG. 4 is a cross-sectional view of the laminated glass according to the first embodiment. [Diagram 5] FIG. 5 is a cross-sectional view showing one configuration example of the light adjusting member. [Figure 6] FIG. 6 is a cross-sectional view of the laminated glass according to the second embodiment. [Figure 7] FIG. 7 is a cross-sectional view of the laminated glass according to the third embodiment. [Figure 8] FIG. 8 is a cross-sectional view of the laminated glass according to the fourth embodiment. [Figure 9] FIG. 9 is a cross-sectional view of the laminated glass according to the fourth embodiment. [Figure 10] FIG. 10 is a cross-sectional view of the laminated glass according to the fifth embodiment. [Figure 11] FIG. 11 is a flow chart showing a method for producing laminated glass according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In this specification, "cross section" refers to the cut surface when the laminated glass is cut in the thickness direction. Furthermore, "periphery" refers to the outermost edge of a specific member, and "periphery" refers to the vicinity of the "periphery". When a specific member is frame-shaped with width, the "periphery" is also called the "outer edge" and may be distinguished from the "inner edge", which is the inner peripheral edge. "Same shape" and "same size" refer to having the same shape and the same dimensions as seen by the human eye. And, unless otherwise specified, "approximately" means the same as seen by the human eye. Note that "~" indicating a numerical range includes the upper and lower limits.

[0012] The laminated glass of the present invention is arranged in, for example, window panes of buildings, showcases, transparent partitions, vehicle windows, and other locations where external light is incident (for example, windshields, side windows, quarter windows, roofs, rear windows, extra windows arranged further rearward than the rear window of a vehicle, etc.), and can control the amount of light incident on the inside of a building, vehicle, etc.

[0013] In the following, an example of using the laminated glass of the present invention as, for example, a side window of a vehicle will be described, but the present invention is not limited thereto. Note that the vehicle is a moving body having a laminated glass, typically an automobile, but including trains, ships, aircraft, etc. Also, the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not accurately represent the size or scale of the actual product.

[0014] (First embodiment) The first embodiment will be described below with reference to Figures 1 to 4. Figure 1 is a perspective view of a laminated glass according to the first embodiment of the present invention, and is also a perspective view showing second to fifth embodiments described below.

[0015] Fig. 1 is a perspective view of a laminated glass 100 according to this embodiment. In Fig. 1, when the laminated glass 100 is attached to a vehicle, the front-rear direction of the vehicle is the X-axis direction, the up-down direction of the vehicle is the Y-axis direction, and the direction perpendicular to the XY plane is the Z-axis direction (this also applies to the following figures). However, when the laminated glass 100 is used for, for example, a windshield, the left-right direction of the vehicle on which the laminated glass 100 is mounted may be interpreted as the X-axis direction, the up-down direction of the vehicle is the Y-axis direction, and the direction perpendicular to the XY plane may be interpreted as the Z-axis direction, as long as the effect of the invention is not impaired.

[0016] The laminated glass 100 according to the present embodiment includes a first glass plate 11 and a second glass plate 12 having substantially the same main surface, a bonding portion 20 disposed between them, and a seal member 40 on the periphery of the bonding portion 20. The first glass plate 11, the bonding portion 20, and the second glass plate 12 are laminated in this order. The central axis (not shown) of the laminated glass 100 is a virtual line in the thickness direction passing through the center of gravity G of the laminated glass 100. In FIG. 1, the laminated glass 100 is curved only in the Y-axis direction, but it may be curved in the X-axis direction, or may be curved in both the X-axis direction and the Y-axis direction. In FIG. 1, the convex surface of the first glass plate 11 and the concave surface of the second glass plate 12 face each other, but the opposite may be true as long as the concave surface of one glass plate faces the convex surface of the other glass plate.

[0017] As shown in FIG. 1, the laminated glass 100 has a substantially trapezoidal shape in plan view, but is not limited thereto. The laminated glass 100 may have, for example, a substantially triangular shape or a substantially rectangular shape depending on the object to be mounted and the portion of the object. Here, "substantially" indicates that the distinction between straight lines and curves, whether the sides are parallel or not, the angle of the apex, and the like are not strictly defined. Hereinafter, the plan view refers to a predetermined area of ​​the laminated glass 100 viewed from the normal direction (positive direction of the Z axis) of the surface of the first glass sheet 11 opposite to the second glass sheet 12. Also, the cross-sectional view refers to a view from a direction perpendicular to a predetermined cross section of the laminated glass.

[0018] At least a portion of the cross section in the vertical direction (Y-axis direction) of the laminated glass 100 may be a wedge shape with a gradually decreasing thickness. A laminated glass having a wedge shape in which at least a portion of the cross section in the vertical direction becomes thicker from bottom to top is suitable for functioning as a head-up display (HUD), and is particularly suitable for use as a windshield. For the laminated glass 10 to have such a cross-sectional shape, at least one of the first glass plate 11, the second glass plate 12, and the adhesive portion 20 may have at least a portion in the vertical direction that is approximately wedge-shaped in cross section.

[0019] The laminated glass 100 according to this embodiment includes a light control member 30 inside the adhesive part 20. The light control member 30 is connected to a power supply body 50. In a plan view, the light control member 30 is disposed inside the sealing member 40, and the periphery of the light control member 30 is adjacent to the inner edge of the sealing member 40. The light control member 30 has two main surfaces, and the main surface on the first glass plate 11 side is referred to as the first main surface, and the main surface on the second glass plate 12 side is referred to as the second main surface. When simply referring to the main surface of the light control member 30, this refers to at least one of the first main surface and the second main surface.

[0020] The adhesive portion 20 includes at least one of a curable transparent resin also called Optical Clear Resin (OCR) and a transparent adhesive sheet also called Optical Clear Adhesive (OCA). The curable transparent resin and the transparent adhesive sheet are members having an adhesive property with a 90° peel strength (N / 25mm) of 0.01N / 25mm or more at 25°C, preferably 0.1N / 25mm or more. The curable transparent resin is liquid at room temperature around 25°C (see the shear viscosity described later), so it can fill the gap between the glass and the adherend, and also exhibits the above-mentioned adhesive strength after curing, so a high-temperature and high-pressure treatment process is not essential for bonding glass plates together. The transparent adhesive sheet can be attached to the surface of a glass plate at room temperature around 25°C and can be pasted by removing interfacial air bubbles, so similarly, a high-temperature and high-pressure treatment process is not essential for bonding glass plates together. Therefore, the light adjusting member 30 is less likely to deform, and deviation in the thickness of the light adjusting member 30, which should maintain a uniform thickness, is also less likely to occur, so that color unevenness can be reduced.

[0021] The 90° peel strength test at 25°C can be performed based on JIS Z 0237:2009. For example, for a curable transparent resin, the 90° peel strength test at 25°C can be performed as follows. First, a frame-shaped spacer with a thickness of 0.5 mm is inserted between a PET film with a thickness of 100 μm that has been subjected to a release treatment on one side and a PET film with a thickness of 100 μm that has not been subjected to a release treatment. Next, the curable transparent resin before curing is poured between the two PET films, and then cured to form a resin sheet with a thickness of 0.5 mm. Then, the obtained resin sheet is cut to the above-mentioned JIS standard size, and the PET film with the release treatment is peeled off. Finally, the peeled surface of the resin sheet is attached to an aluminosilicate glass, and a 90° peel test is performed at 25°C with the PET film with a thickness of 100 μm that has not been subjected to a release treatment still attached. The type of PET film does not matter, but for example, "Lumirror (registered trademark)" may be used.

[0022] The curable transparent resin is in a liquid state at room temperature and normal pressure before curing. The curable transparent resin is preferably in a handling state if its shear viscosity at 25°C at room temperature and normal pressure before curing is 100 mPa·s or more, and is preferably 100,000 mPa·s or less since the liquid spreads easily. At the stage of forming a laminate in which the first glass plate 11, the adhesive portion 20, and the second glass plate 12 are laminated in this order, the adhesive portion 20 including the light control member 30 is easily adapted to a desired shape, so that it is preferable that the adhesive portion 20 contains a curable transparent resin. By containing the curable transparent resin, the light control member 30 is less likely to deform and thickness deviation is less likely to occur, so that color unevenness can be reduced.

[0023] The sealing member 40 is a member provided in a frame shape to prevent at least one of the curable transparent resin and the transparent adhesive sheet contained in the adhesive part 20 from protruding outside the glass plate. Here, the "inside" refers to the central axis direction passing through the center of gravity G of the laminated glass 100 when viewed from the periphery of a specific member (for example, the first glass plate 11). Conversely, the "outside" refers to the periphery direction of the specific member (the first glass plate 11) when viewed from the central axis passing through the center of gravity G of the laminated glass 100. In FIG. 1, the dotted line indicates the periphery of the light control member 30, and the dashed-dotted line indicates the inner edge of the sealing member 40.

[0024] In a plan view, the sealing member 40 overlaps with the entire periphery of the first glass plate 11 and the second glass plate 12. However, it is sufficient that the sealing member 40 overlaps with at least a part of the periphery of the first glass plate 11 or the second glass plate 12. Specifically, when the periphery of the first glass plate 11 is located inside the periphery of the second glass plate 12, the sealing member 40 may overlap only with the periphery of the first glass plate 11.

[0025] The planar shape of the light control member 30 is substantially similar to that of the first glass plate 11 in FIG. 1, but may be substantially circular, elliptical, triangular, rectangular, trapezoidal, or n-sided (n is an integer of 5 or more), etc. The power supply body 50 is usually made of a flexible material. The power supply body 50 may be electrically connected directly to the light control member 30, or may be electrically connected via a transparent conductive film or a foil-like conductor called a bus bar. The connection method may be any known means.

[0026] The laminated glass 100 may include a strip-shaped light-shielding portion on the periphery of at least one of the first glass plate 11 and the second glass plate 12. The light-shielding portion can completely or partially conceal the periphery of the light-adjusting member 30, the sealing member 40, the power supply body 50, and the attachment portion to the vehicle frame or the like. The light-shielding portion can also suppress deterioration of the sealing member 40 and the urethane resin used to bond the laminated glass 100 to the vehicle due to ultraviolet rays or the like.

[0027] FIG. 2 is a cross-sectional view of the laminated glass 100 of FIG. 1 cut on the XZ plane at the position X1-X2 of FIG. 1, viewed from the Y-axis direction (hereinafter also referred to as "X1-X2 cross-sectional view"). In this embodiment, the adhesive portion 20 has only the first adhesive layer 21. The first adhesive layer 21 is in contact with the first glass plate 11, the second glass plate 12, the light control member 30, and the seal member 40. The first adhesive layer 21 is in contact with the first main surface, the second main surface, and the side surface (i.e., the entire surface) of the light control member 30. Therefore, even if a laminate including the light control member 30 is pressurized in a manufacturing process in which the adhesive portion 20 and other members are bonded to form the laminated glass 100, the first adhesive layer 21 is less likely to flow than when the first adhesive layer 21 is in contact with only a part of the surface (for example, the main surface of the light control member 30), and therefore stress is less likely to be applied to the light control member 30. As a result, color unevenness can be reduced. The first adhesive layer 21 may have either a transparent adhesive sheet or a curable transparent resin, but preferably has a curable transparent resin that is less likely to apply stress to the light adjusting member 30.

[0028] The seal member 40 contacts the first glass plate 11 and the second glass plate 12. In a plan view, the seal member 40 overlaps the entire periphery of the first glass plate 11 and the second glass plate 12, and the first adhesive layer 21 is unlikely to protrude from the periphery of the laminated glass 100. Therefore, the task of removing the protruding adhesive portion 20 can be omitted.

[0029] A light-shielding portion 61 may be provided on the periphery of the main surface (concave surface) of the first glass plate 11 opposite the light-adjusting component 30, and a light-shielding portion 62 may be provided on the periphery of the main surface (concave surface) of the second glass plate 12 on the side of the light-adjusting component 30. The light-shielding portion 61 and the light-shielding portion 62 may also be provided in the following Figs. 3 and 4.

[0030] 3 is (a) a plan view and (b) an X1-X2 cross-sectional view of the laminated glass 100 in FIG. 1. The seal member 40 may have one or more gaps S in which the seal member 40 is not partially in contact with at least one of the first glass sheet 11 and the second glass sheet 12. For example, the seal member 40 may be partially in contact with the second glass sheet 12 without being partially in contact with the first glass sheet 11. Alternatively, the seal member 40 may be partially out of contact with both the first glass sheet 11 and the second glass sheet 12.

[0031] The gap S is provided in a part of the seal member 40, separate from the portion through which the power feeder 50 passes, and can be used as a hole for forming the adhesive portion 20 by injecting a resin, for example. The gap S can also release air bubbles in the adhesive portion 20 and pressure applied to the adhesive portion 20 when the glass plates are bonded together. Since the gap S exists only partially, even if the first adhesive layer 21 protrudes from the periphery of the first glass plate 11 and the second glass plate 12, it is easy to remove. The gap S is preferably provided when the first adhesive layer 21 contains a curable transparent resin.

[0032] Fig. 4 is a cross-sectional view of the laminated glass 100 in Fig. 1 cut on the YZ plane at the position Y1-Y2 in Fig. 1, as viewed from the X-axis direction (hereinafter also referred to as "Y1-Y2 cross-sectional view"). The power supply body 50 is sandwiched between the adhesive part 20 and the seal member 40. One end of the power supply body 50 is connected to the light-adjusting member 30. The other end of the power supply body 50 is connected to an external power source such as a vehicle battery, and the light-adjusting member 30 is supplied with power.

[0033] 1 and 4, one power supply body 50 is connected to a side surface (XZ plane) of the light control member 30, but multiple power supply bodies 50 may be connected. For example, multiple power supply bodies 50 may be connected to the same side surface of the light control member 30, multiple power supply bodies 50 may be connected to different side surfaces, or multiple power supply bodies 50 may be connected to a surface including a surface different from the side surface. In other words, the power supply body 50 may be connected to any main surface of the light control member 30 as long as it extends in any direction of the XY plane.

[0034] 5 is a cross-sectional view showing an example of the configuration of a light control member 30 that can be used in the laminated glass 100 according to the first embodiment. The light control member 30 has a light control element 78 between a first base material 71 provided with a first conductive layer 75 and a second base material 72 provided with a second conductive layer 76. The periphery of the light control element 78 is in contact with a sealant 79.

[0035] The first substrate 71 and the second substrate 72 are sheet-like dielectric materials made of transparent materials, and are preferably flexible. In the laminated glass 100 according to the first embodiment, it can be arbitrarily selected which side of the first glass plate 11 and the second glass plate 12 the first substrate 71 and the second substrate 72 face. For example, the light control member 30 may be disposed so that the first substrate 71 faces the first glass plate 11, and the second substrate 72 faces the second glass plate 12.

[0036] The first conductive layer 75 and the second conductive layer 76 are preferably transparent to such an extent that the other side can be seen from at least one side of the light adjusting member 30. Note that, although the first conductive layer 75 and the second conductive layer 76 are formed over the entire surfaces of the first substrate 71 and the second substrate 72 in Fig. 5, they may be formed only in partial regions of the first substrate 71 and the second substrate 72.

[0037] In addition, in the light control member 30, a pair of electrodes included in the power supply body 50 shown in FIG. 1 and FIG. 4 are electrically connected to the first conductive layer 75 and the second conductive layer 76, respectively. The light control element 78 has liquid crystal, and the visible light transmittance changes when a voltage is applied between the first conductive layer 75 and the second conductive layer 76. The light control element 78 may be an element that operates in a so-called normal mode in which the visible light transmittance is high when a voltage is applied (bright state) and the visible light transmittance is low when a voltage is not applied (dark state), or an element that operates in a reverse mode. The light control element 78 may appropriately include a dichroic dye, a spacer, and the like. Note that the sealing material 79 may be provided as necessary, but may not be provided.

[0038] Second embodiment 6 is an X1-X2 cross-sectional view of a laminated glass 200 according to the second embodiment. In this embodiment, differences from the laminated glass 100 according to the first embodiment will be described, and the description of the first embodiment will be used for the rest. This embodiment differs from the first embodiment in that the adhesive portion 20 has a first adhesive layer 21 and a second adhesive layer 22.

[0039] In this embodiment, the adhesive portion 20 has a first adhesive layer 21 and a second adhesive layer 22, and the first glass plate 11, the first adhesive layer 21, the second adhesive layer 22, and the second glass plate 12 are laminated in this order. The first adhesive layer 21 contacts the first glass plate 11, the second adhesive layer 22, the seal member 40, and the first main surface and side surface of the light control member 30. The second adhesive layer 22 contacts the second glass plate 12, the first adhesive layer 21, the seal member 40, and the second main surface of the light control member 30. The entire surface of the light control member 30 is held by the first adhesive layer 21 and the second adhesive layer 22. The first adhesive layer 21 contacts all of the first main surface and side surface of the light control member 30, and the second adhesive layer 22 contacts all of the second main surface of the light control member 30.

[0040] The first adhesive layer 21 and the second adhesive layer 22 may each have either a curable transparent resin or a transparent adhesive sheet, but in order to prevent stress from being applied to the light control member 30, it is preferable that at least one of the first adhesive layer 21 and the second adhesive layer 22 has a curable transparent resin. For example, the first adhesive layer 21 may have a curable transparent resin, and the second adhesive layer 22 may have a transparent adhesive sheet. The light control member 30 can significantly reduce color unevenness by having the side surface held by the curable transparent resin. In addition, when the main surface of the light control member 30 is in contact with a transparent adhesive sheet corresponding to the second adhesive layer 22, the position is less likely to shift when bonding glass plates together.

[0041] Furthermore, for example, the first adhesive layer 21 and the second adhesive layer 22 may both have a curable transparent resin. By using a curable transparent resin for these adhesive layers, it is easy to adjust the position of the light control member 30 in the Z-axis direction. The respective adhesive layers (e.g., two curable transparent resins) may be made of the same material or different materials. If they are made of the same material, the boundary between the first adhesive layer 21 and the second adhesive layer 22 is less noticeable. If they are made of different materials, when the laminated glass 200 is attached to a vehicle, the adhesive layer located on the outer side of the vehicle and the adhesive layer located on the inner side of the vehicle can have different properties.

[0042] 6, the contact interface between the first adhesive layer 21 and the second adhesive layer 22 is on the same plane as the second main surface of the light control member 30, but is not limited thereto. The contact interface between the first adhesive layer 21 and the second adhesive layer 22 may be on the same plane as the first main surface of the light control member 30, for example, or may be at any position between the second main surface and the first main surface of the light control member 30.

[0043] In order to prevent stress concentration on the light-adjusting component 30, it is preferable that at least a part of the side surface of the light-adjusting component 30 is in contact with an adhesive layer containing a curable transparent resin (e.g., the first adhesive layer 21). Of the total area of ​​the side surface of the light-adjusting component 30, the area in contact with the adhesive layer containing a curable transparent resin is preferably 20% or more, more preferably 50% or more, even more preferably 70% or more, and particularly preferably 95% or more.

[0044] Third embodiment 7 is an X1-X2 cross-sectional view of laminated glass 300 according to the third embodiment. In this embodiment, differences from laminated glass 200 according to the second embodiment will be described, and the description of the second embodiment will be used for the rest. This embodiment differs from the second embodiment in that the second adhesive layer 22 is not in contact with the seal member 40.

[0045] In this embodiment, the first glass plate 11, the first adhesive layer 21, and the second glass plate 12 are laminated in this order. The first glass plate 11, the light control member 30, the second adhesive layer 22, and the second glass plate 12 are laminated in this order. The first adhesive layer 21 contacts the first main surface and the side surface of the light control member 30, and the second adhesive layer 22 contacts the second glass plate 12, the first adhesive layer 21, and the second main surface of the light control member 30. In the laminated glass 300 according to this embodiment, as in the laminated glass 200 according to the second embodiment, the entire surface of the light control member 30 is held by the first adhesive layer 21 and the second adhesive layer 22, thereby reducing color unevenness. The first adhesive layer 21 contacts the entire first main surface and the entire side surface of the light control member 30, and the second adhesive layer 22 contacts the entire second main surface of the light control member 30.

[0046] In the laminated glass 300 shown in FIG. 7 , the periphery of the second adhesive layer 22 (in a plan view) coincides with the periphery of the light control member 30, but this does not necessarily have to be the case. For example, in a plan view, the periphery of the second adhesive layer 22 may be located inside or outside the periphery of the light control member 30. Furthermore, the second adhesive layer 22 may be partially in contact with the seal member 40, as in the laminated glass 200. In this case, both the first adhesive layer 21 and the second adhesive layer 22 are in contact with the second glass plate 12.

[0047] Furthermore, in plan view, the periphery of the second adhesive layer 22 may be adjusted so that it does not overlap the light-shielding portion 62, is in contact with the light-shielding portion 62, or slightly overlaps with the light-shielding portion 62. In this way, by adjusting the position of the periphery of the second adhesive layer 22, it is possible to easily use a plurality of transparent resins appropriately, such as using a photocurable transparent resin for the second adhesive layer 22 and a non-photocurable transparent resin for the first adhesive layer 21. Note that when the second adhesive layer 22 contains a curable transparent resin, a separate seal member (not shown) may be provided on the periphery of the second adhesive layer 22.

[0048] (Fourth embodiment) 8 is a cross-sectional view taken along the X1-X2 line of the laminated glass 400 according to the fourth embodiment. In this embodiment, differences from the laminated glass 200 according to the second embodiment will be described, and the description of the second embodiment will be used for the rest. This embodiment differs from the second embodiment in that the seal member 40 is not in contact with the second glass plate 12.

[0049] In this embodiment, the seal member 40 is in contact with the first glass plate 11, the first adhesive layer 21, and the second adhesive layer 22. In plan view, the second adhesive layer 22 overlaps the entire surface of the second glass plate 12, and the periphery of the second adhesive layer 22 coincides with the periphery of the second glass plate 12 (the first glass plate 11). Therefore, the installation position of the second adhesive layer 22 with respect to the second glass plate 12 can be easily determined. In this embodiment, the second adhesive layer 22 is not in contact with the inner edge of the seal member 40, and is exposed to the outside of the laminated glass 400. Therefore, in this embodiment, the second adhesive layer 22 is preferably a transparent adhesive sheet. The first adhesive layer 21 is in contact with all of the first main surface and side surfaces of the light control member 30, and the second adhesive layer 22 is in contact with all of the second main surface of the light control member 30.

[0050] 9 is a Y1-Y2 cross-sectional view of a laminated glass 400 according to the fourth embodiment. In this embodiment, the power supply body 50 is sandwiched between the first adhesive layer 21 and the second adhesive layer 22 of the adhesive part 20, and is further sandwiched between the seal member 40 and the second adhesive layer 22. Since the second adhesive layer 22 is arranged parallel to the light control member 30 and up to the peripheral edge of the second glass plate 12, the power supply body 50 can be easily arranged parallel to the light control member 30 (on approximately the same plane). Furthermore, since the power supply body 50 is not sandwiched between the seal members 40, the seal members 40 can be easily formed.

[0051] Fifth embodiment FIG. 10 is a Y1-Y2 cross-sectional view of the laminated glass 500 according to the fifth embodiment. In this embodiment, differences from the laminated glass 200 according to the second embodiment will be described, and the description of the second embodiment will be used for the rest. This embodiment differs from the second embodiment in that the adhesive portion 20 has a third adhesive layer 23 between the light control member 30 and the second adhesive layer 22, and has a resin film 26 between the second adhesive layer 22 and the third adhesive layer 23. The power supply body 50 is sandwiched between the first adhesive layer 21 and the seal member 40. The first adhesive layer 21 contacts the entire first main surface and side surface of the light control member 30, and the third adhesive layer 23 contacts the entire second main surface of the light control member 30.

[0052] The third adhesive layer 23 has either a curable transparent resin or a transparent adhesive sheet. The third adhesive layer 23 is disposed between the light control member 30 and the resin film 26, and bonds them together. In FIG. 10, the third adhesive layer 23 is in contact with only a part of the resin film 26, but may be in contact with the entire surface. The resin film 26 is, for example, a resin film having at least an ultraviolet absorbing function or an ultraviolet reflecting function. The liquid crystal molecules of the light control element 78 may deteriorate due to exposure to ultraviolet light, and the amount of change in the visible light transmittance of the light control member 30 when a voltage is applied / not applied may become small. In order to reduce the deterioration of the light control element 78, the resin film 26 preferably has an ultraviolet absorbing function or an ultraviolet reflecting function. The resin film 26 may have an infrared absorbing function or an infrared reflecting function.

[0053] In FIG. 10, the resin film 26 is in contact with the inner edge of the seal member 40. In addition, in a plan view, the periphery of the resin film 26 may coincide with the periphery of the dimming member 30, but is preferably located outside the periphery of the dimming member 30. The dimming member 30 is also protected from ultraviolet light that has been scattered or otherwise circumvented, and deterioration can be reduced. The impact resistance of the laminated glass 500 at the periphery of the dimming member 30 is improved. Furthermore, the resin film 26 may be disposed such that the periphery of the resin film 26 coincides with the periphery of the second glass plate 12 (first glass plate 11) as in the second adhesive layer 22 in the fourth embodiment. In this case, the impact resistance of the laminated glass 500 as a whole is improved.

[0054] When the resin film 26 does not contact the inner edge of the seal member 40, the first adhesive layer 21 and the second adhesive layer are in contact with each other. The second adhesive layer 22 may not be in contact with the seal member 40 partially, as in the case of the laminated glass 300. In this case, both the first adhesive layer 21 and the second adhesive layer 22 are in contact with the second glass plate 12. When the resin film 26 does not contact the inner edge of the seal member 40, the first adhesive layer 21 may be disposed in the portion where the second adhesive layer 22 is disposed in FIG. 10. In this case, the third adhesive layer 23 may be the second adhesive layer 22.

[0055] 1 to 10 have been used to explain the laminated glasses 100 to 500 according to an embodiment of the present invention, but the laminated glasses 100 to 500 may include a polarizing plate, a color filter, a spacer, etc., as necessary. The spacer is preferably provided in the curable transparent resin portion of the adhesive part 20, and can make it easier to keep at least one of the distance between the first glass plate 11 and the light control member 30 and the distance between the second glass plate 12 and the light control member 30 constant.

[0056] <Each component> Next, each of the components included in the laminated glasses 100 to 500 according to one embodiment of the present invention will be described in more detail. For the sake of simplicity, the laminated glasses 100 to 500 will be described as the laminated glass 100, but the following description of each component can also be applied to the laminated glasses 200 to 500. Therefore, the reference symbols used in Figs. 1 to 10 will be used to describe each component.

[0057] <Glass plate> The first glass plate 11 and the second glass plate 12 may have any shape, but are preferably rectangular, trapezoidal, or triangular. The first glass plate 11 and the second glass plate 12 may be flat, but it is preferable that at least one of them is curved, and it is more preferable that both are curved. The first glass plate 11 and the second glass plate 12 may each be a single curved shape (cylindrical) that is curved in a single direction, or a complex curved shape that is curved in two perpendicular directions.

[0058] In the laminated glass 100, the radius of curvature of the first glass plate 11 may be substantially the same as (including the case where both are flat plates) or different from the radius of curvature of the second glass plate 12. For example, the radius of curvature of the first glass plate 11 may be larger than the radius of curvature of the second glass plate 12. That is, the ratio of the smallest radius of curvature (R2) of the second glass plate 12 to the smallest radius of curvature (R1) of the first glass plate 11 may be 1≦R1 / R2. At this time, the convex surface of the first glass plate 11 faces the concave surface of the second glass plate 12. Conversely, when 1≧R1 / R2, the concave surface of the first glass plate 11 faces the convex surface of the second glass plate 12.

[0059] When R1 and R2 are substantially the same, either the first glass plate 11 or the second glass plate 12 may be arranged on the vehicle interior / vehicle exterior side. When R1 and R2 are different, in order to prevent the glass plates from contacting each other during manufacturing and causing distortion, among R1 and R2, the glass plate corresponding to the larger value is preferably arranged on the vehicle interior side, and the glass plate corresponding to the smaller value is preferably arranged on the vehicle exterior side. That is, for example, when R2<R1, the first glass plate 11 is preferably arranged on the vehicle interior side, and the second glass plate 12 is preferably arranged on the vehicle exterior side.

[0060] As the first glass plate 11 and the second glass plate 12, conventionally known inorganic glass and organic glass used for vehicle window glass can be selected. The composition of the first glass plate 11 and the composition of the second glass plate 12 may be the same or different. As the inorganic glass, soda-lime glass, aluminosilicate glass, borosilicate glass, alkali-free glass, quartz glass, etc. are used without particular limitation.

[0061] The glass plate located on the outer side of the laminated glass 100 is preferably inorganic glass from the viewpoint of scratch resistance, and soda-lime glass from the viewpoint of formability. When the glass plate is soda-lime glass, clear glass, green glass containing a predetermined amount or more of iron components, and UV-cut green glass can be suitably used. The UV-cut green glass plate refers to an ultraviolet absorbing green glass containing 68% to 74% by mass of SiO2, 0.3% to 1.0% by mass of Fe2O3, and 0.05% to 0.5% by mass of FeO, and having an ultraviolet transmittance of 1.5% or less at a wavelength of 350 nm and a minimum transmittance value in the range of 550 nm to 1700 nm.

[0062] These are manufactured by any known method such as a float method, a fusion method, a roll-out method, a down-draw method, etc. Gravity forming, press forming, roller forming, etc. are used for bending the inorganic glass, and the glass sheet is bent at about 550° C. to 770° C. The inorganic glass may be untempered glass obtained by forming molten glass into a sheet and slowly cooling it, and may be subjected to a strengthening treatment such as physical strengthening (for example, air-cooling strengthening) or chemical strengthening, as necessary.

[0063] Examples of the organic glass include transparent resins such as polycarbonate resin, acrylic resin, polystyrene resin, aromatic polyester resin, polyester resin, polyarylate resin, polycondensation product of halogenated bisphenol A and ethylene glycol, acrylic urethane resin, and halogenated aryl group-containing acrylic resin. The organic glass is preferably polycarbonate because it can provide a lightweight and flexible sheet. The above resins may be used in combination of two or more kinds.

[0064] Float glass is more preferable for the first glass plate 11 and the second glass plate 12. The float glass is usually preferably soda lime glass, but alkali-free glass may be used, for example, to transmit radio waves of a predetermined frequency.

[0065] Both inorganic glass and organic glass are usually colorless, but may be colored as long as they are transparent. In the case of color, they may be so-called privacy glass, which has a dark color such as gray. Privacy glass is described in detail in, for example, International Publication No. 2015 / 088026, the contents of which are incorporated herein by reference. Privacy glass has the effect of reducing the transmission of sunlight from the outside of the vehicle to the inside of the vehicle and improving the aesthetics from the inside and outside of the vehicle while making it difficult to see inside the vehicle from the outside.

[0066] The privacy glass is preferably used for parts other than the windshield, particularly the roof, the side windows at the rear of the vehicle, the rear window, etc. Furthermore, the inorganic glass and the organic glass may have an infrared absorbing function and an ultraviolet absorbing function.

[0067] The thicknesses of the first glass sheet 11 and the second glass sheet 12 can be appropriately selected depending on the type and location of the automobile in which the laminated glass 100 is used, but generally can be 0.1 mm to 10 mm, respectively. Hereinafter, the thicknesses of the first glass sheet 11 and the second glass sheet 12 will be described assuming that, when the laminated glass 100 is attached to a vehicle, the first glass sheet 11 is disposed on the inside of the vehicle, and the second glass sheet 12 is disposed on the outside of the vehicle. When the thickness of the glass sheets varies, the thickness is the thickness of the thinnest part.

[0068] From the viewpoint of resistance to flying stone impact, the thickness of the first glass plate 11 is preferably 0.3 mm or more, more preferably 0.5 mm or more, even more preferably 0.7 mm or more, particularly preferably 1.1 mm or more, and most preferably 1.6 mm or more. In order to reduce the mass of the laminated glass 100, the thickness of the first glass plate 11 is preferably 3 mm or less, more preferably 2.6 mm or less, and even more preferably 2.1 mm or less.

[0069] The same can be said about the second glass plate 12 as about the first glass plate 11. The second glass plate 12 may have a different composition from that of the first glass plate 11. The second glass plate 12 may also have a different thickness from that of the first glass plate 11.

[0070] When the first glass plate 11 and the second glass plate 12 have different thicknesses, it is preferable in terms of resistance to flying stone impact if the glass plate located on the outer side of the vehicle has a thickness greater than that of the glass plate located on the inner side of the vehicle. The difference in thickness between the first glass plate 11 and the second glass plate 12 is preferably 0.3 to 1.5 mm, more preferably 0.5 to 1.3 mm.

[0071] A coating that imparts water repellency, hydrophilicity, antifouling, anti-fingerprint, anti-fogging, electrothermal, infrared absorbing / reflecting, ultraviolet absorbing / reflecting, low radiation, low reflection, coloring, etc. may be provided on the main surface of at least one of the first glass plate 11 and the second glass plate 12. These coatings may be used alone or in combination. Furthermore, instead of the coating, a film exhibiting similar functions, characteristics, etc. may be attached to the main surface of the glass plate.

[0072] Of the first glass plate 11 and the second glass plate 12, it is preferable to provide a coating that imparts a water-repellent function, a hydrophilic function, or an antifouling function to the main surface that is the outermost side of the vehicle when the first glass plate 11 and the second glass plate 12 are attached to the vehicle. It is also preferable to provide a coating that imparts an electric heat function, an infrared absorbing / reflecting function, an ultraviolet absorbing / reflecting function, or coloring to at least one of the opposing main surfaces (the main surface on the light control member 30 side) of the first glass plate 11 and the second glass plate 12. In particular, it is preferable that the coating that imparts an infrared absorbing / reflecting function or an ultraviolet absorbing / reflecting function is applied to the main surface of the glass plate (e.g., the second glass plate 12) located on the outer side of the vehicle, on the inner side of the vehicle. Of the first glass plate 11 and the second glass plate 12, it is preferable to provide a coating that imparts an anti-fingerprint function, an anti-fogging function, an electric heat function, an infrared absorbing / reflecting function, a low radiation characteristic, a low reflection characteristic, or coloring to the main surface that is the innermost side of the vehicle when the first glass plate 11 and the second glass plate 12 are attached to the vehicle.

[0073] <Light shielding part> The light-shielding parts 61 and 62 are configured as, for example, opaque layers, but only need to be able to block visible light to the extent that it can be concealed at least in the areas that need to be concealed. For example, the light-shielding parts 61 and 62 may be configured of organic ink, colored ceramics, colored film, or the like. The light-shielding parts 61 and 62 may be any color, such as white, gray, black, brown, or dark blue, with dark colors being preferable, and black being more preferable.

[0074] The thickness of the light shielding parts 61 and 62 is not particularly limited, but may be, for example, in the range of 1 μm to 200 μm, and preferably 5 μm to 150 μm. When the light shielding parts 61 and 62 are made of organic ink or colored ceramics, the thickness of the light shielding parts 61 and 62 is more preferably 5 μm to 30 μm.

[0075] 2 to 4 and 6 to 10, the light-shielding portions 61, 62 are provided on the periphery of the first glass plate 11 and the second glass plate 12 in the laminated glasses 100 to 500, but this is not essential. For example, only one of the light-shielding portions 61, 62 may be provided, or neither may be provided.

[0076] 2 to 4 and 6 to 10, the light-shielding portion 61 is provided on the main surface (concave surface) of the first glass plate 11 opposite the light-adjusting member 30, and the light-shielding portion 62 is provided on the main surface (concave surface) of the second glass plate 12 facing the light-adjusting member 30. In this way, when the glass plate is curved, the light-shielding portion is usually provided on the concave surface. In other words, when the laminated glass 100 is attached to a vehicle, the light-shielding portion is preferably provided on the main surface on the vehicle interior side of at least one of the first glass plate 11 and the second glass plate 12.

[0077] <Adhesive parts and adhesive layers> The adhesive portion 20 includes at least one adhesive layer and bonds a plurality of glass plates together. The adhesive layer includes a curable transparent resin or a transparent adhesive sheet. For the curable transparent resin and the transparent adhesive sheet, for example, acrylate-based, silicone-based, acrylic-modified silicone-based, urethane-based, urethane acrylate-based, epoxy-based, epoxy acrylate-based, acrylamide-based, or methacrylamide-based resin compositions can be used. The curable transparent resin is a liquid (before curing) obtained by adjusting the viscosity of the resin composition to be easily discharged without adding a solvent. The transparent adhesive sheet is a solid (viscoelastic body) obtained by applying the resin composition evenly onto a releasable sheet and curing it with light or heat.

[0078] These curable transparent resins and transparent adhesive sheets may be used alone or in combination of two or more kinds. For example, by using an acrylic resin composition and a silicone resin composition in combination, the acrylic resin composition absorbs moisture that has infiltrated from the outside of the laminated glass 100 preferentially over the silicone resin composition, and the clouding of the silicone resin composition due to moisture can be reduced. Therefore, the aesthetics of the laminated glass 100 can be easily maintained for a long time. The transparent adhesive sheet includes one in which adhesive is provided on both sides of a base sheet, and one in which the entire sheet is made of adhesive without a base sheet.

[0079] The curable transparent resin may be any of a thermosetting type, a photosetting type, and a room temperature curing type from the viewpoint of the curing method, and these resins may be cured and used when bonding glass plates. From the viewpoints of workability and productivity, the curable transparent resin is preferably a photosetting type or a room temperature curing type, and more preferably a room temperature curing type in that it can also cure shielding parts such as prints.

[0080] From the viewpoints of optical transparency and heat resistance, it is preferable to use a photocurable transparent resin based on an acrylate, urethane acrylate, epoxy acrylate, etc. The light used for photocuring may be ultraviolet light or visible light, and can be generated using, for example, a metal halide UV lamp, an LED lamp, a high-pressure mercury lamp, an electrodeless lamp, a xenon lamp, or the like.

[0081] The photocurable transparent resin may contain a photopolymerization initiator. Examples of the photopolymerization initiator include an ultraviolet polymerization initiator or a visible light polymerization initiator. Examples of the ultraviolet polymerization initiator include a benzoin-based initiator, a benzophenone-based initiator, and an acetophenone-based initiator. Examples of the visible light polymerization initiator include an acylphosphine oxide-based initiator, a thioxanthone-based initiator, a metallocene-based initiator, a quinone-based initiator, and an α-aminoalkylphenone-based initiator.

[0082] The photocurable transparent resin may contain a silane coupling agent, which can improve adhesion and adhesion stability, improve heat resistance and moisture resistance, and improve adhesion reliability even when left for a long period of time under harsh conditions.

[0083] Examples of the room temperature curing type include a moisture curing type that cures by reacting with moisture in the air, and a reaction curing type that contains at least two types of resin compositions and cures by mixing these resin compositions. As a reaction curing type curable transparent resin, for example, a two-part curable polyorganosiloxane composition described in Japanese Patent No. 5308564 or Japanese Patent No. 5414931 can be used.

[0084] The curable transparent resin may contain additives such as elastomers, highly refractive inorganic nanoparticles, antioxidants, curing agents, plasticizers, fillers, UV stabilizers, color-matching agents, reinforcing agents, antifoaming agents, surfactants, or rust inhibitors, as necessary, depending on the intended use. However, depending on the type of the encapsulated object, it may be deteriorated by a specific plasticizer, and in that case, it is preferable to use a resin that does not substantially contain that plasticizer.

[0085] The thickness of the adhesive portion 20 is preferably 0.5 mm or more at the thinnest part. When the thickness of the adhesive portion 20 at the thinnest part is 0.5 mm or more, the adhesive portion 20 easily disperses stress with small displacement and easily suppresses deformation of the light control member 30, so that color unevenness is unlikely to occur. In addition, the impact resistance required for the laminated glass 100 can be ensured. The thickness of the adhesive portion 20 is preferably 3 mm or less at the thickest part. When the thickness of the adhesive portion 20 at the thickest part is 3 mm or less, the mass of the laminated glass 100 does not become too large. The thickness of the adhesive portion 20 at the thickest part is more preferably 2.8 mm or less, and even more preferably 2.6 mm or less.

[0086] The thickness of the adhesive part 20 refers to the thickness of the adhesive part 20 only, excluding the thickness of the dimming member 30. The thinnest part of the adhesive part 20 refers to, for example, a part that sandwiches the dimming member 30 (a part that overlaps with the dimming member 30 in a planar view). The thickest part of the adhesive part 20 refers to, for example, a part that does not sandwich the dimming member 30 (a part that does not overlap with the dimming element 78 in a planar view).

[0087] When the adhesive portion 20 has a first adhesive layer 21 and a second adhesive layer 22, and the second adhesive layer 22 includes a transparent adhesive sheet, the thickness of the second adhesive layer 22 is preferably 1 μm or more at the thinnest part for easy handling. Furthermore, from the viewpoint of impact resistance, the thickness of the second adhesive layer 22 is more preferably 10 μm or more, and even more preferably 50 μm or more. Furthermore, in order to follow the curved shape of the glass plate, the thickness of the second adhesive layer 22 is preferably 1000 μm or less, and more preferably 500 μm or less. The same applies when the first adhesive layer 21 includes a transparent adhesive sheet.

[0088] The first adhesive layer 21 has a shear modulus of 2.0×10 at 25° C. 5 Pa or less is preferable, and 1.9×10 5 Pa or less is more preferable, and 1.8×10 5 The first adhesive layer 21 has a shear modulus of elasticity of 2.0×10 Pa or less at 25° C. 5 When the elastic modulus is equal to or less than Pa, stress is easily dispersed by small displacement and deformation of the light adjusting member 30 is easily suppressed, so that color unevenness is unlikely to occur.

[0089] The first adhesive layer 21 has a shear modulus of elasticity of 1.0×10 at 25° C. 3 Pa or more is preferable, 5.0×10 3 Pa or more is preferable, and 1.0×10 4 The first adhesive layer 21 has a shear modulus of elasticity of 1.0×10 Pa or more at 25° C. 3 If the shear modulus is equal to or higher than Pa, wrinkles that affect the occurrence of color unevenness during handling are unlikely to occur. The same applies to the second adhesive layer 22. When the adhesive portion 20 has a plurality of adhesive layers, it is preferable that the adhesive layer exhibiting the largest shear modulus of elasticity has a shear modulus within the above range.

[0090] In addition, if the first adhesive layer 21 has a tan δ of 0.1 or more at 25° C., high adhesive strength can be obtained, which is preferable. Furthermore, if the first adhesive layer 21 has a tan δ of 1.0 or less at 25° C., shear peeling can be reduced, which is preferable. The same applies to the second adhesive layer 22. Note that the shear modulus and tan δ in this specification can be measured by subjecting a specimen to a dynamic viscoelasticity test using a shear method, for example, MCR301 manufactured by Anton Paar, under a frequency condition of 1 Hz.

[0091] The adhesive portion 20 (specifically, the adhesive layer included in the adhesive portion 20) may further contain a colorant, an infrared absorbing agent, an ultraviolet absorbing agent, a luminescent agent, and the like. When the laminated glass 100 is attached to a vehicle, the adhesive portion 20 preferably contains at least an ultraviolet absorbing agent in a portion located on the vehicle outer side than the light control member 30. When the adhesive portion 20 contains an ultraviolet absorbing agent, the laminated glass 100 is less likely to have a reduced visible light transmittance even after long-term use. That is, when the adhesive portion 20 contains an ultraviolet absorbing agent, the weather resistance of the laminated glass 100 is improved. In addition, the adhesive portion 20 may have a colored portion called a shade band. When the adhesive portion 20 contains an ultraviolet absorbing agent, the ultraviolet transmittance of the adhesive portion 20 is preferably 20% or less. In addition, the ultraviolet transmittance of at least one of the first adhesive layer 21 and the second adhesive layer 22 is preferably 20% or less.

[0092] The adhesive portion 20 has a visible light transmittance measured in accordance with JIS K7361-1 of preferably 70% or more, more preferably 80% or more. The adhesive portion 20 has a yellowness index calculated in accordance with JIS K7373-2006 of preferably 30 or less, more preferably 20 or less. The value obtained by dividing the yellowness index calculated in accordance with JIS K7373-2006 by the thickness (μm) of the thickest part of the adhesive portion 20 is 0.04 μm. -1 Less than 0.03 μm is preferable. -1 The following is more preferred:

[0093] <Ultraviolet absorbing agent> In order to reduce the deterioration of the light control member 30 (light control element 78) due to ultraviolet rays and maintain the light transmission / light blocking performance of the light control member 30, it is preferable that at least one of the members located on the vehicle outer side than the light control element 78 has an ultraviolet absorbing function. At least one of the first glass plate 11 and the second glass plate 12, the adhesive part 20, the resin film 26, the first base material 71 and the second base material 72 of the light control element has an ultraviolet absorbing function. These members have an ultraviolet absorbing function when they contain an ultraviolet absorbing agent inside. In addition, these members have an ultraviolet absorbing function when they have a coating film containing an ultraviolet absorbing agent on their surface. The transmittance of ultraviolet rays that are incident from one glass plate of the laminated glass 100 so as to pass through the light control member 30 and are emitted from the other glass plate is preferably 0% or more and 20% or less. The wavelength of the ultraviolet rays is, for example, 250 nm to 380 nm, and may include at least 380 nm. If the ultraviolet transmittance is 20% or less, deterioration of the light-adjusting element 78 is reduced, and the light transmitting / light blocking performance of the light-adjusting member 30 is easily maintained. The ultraviolet transmittance is more preferably less than 20%, and further preferably less than 10%.

[0094] The ultraviolet absorbing agent may be a known or well-known one, or a plurality of ultraviolet absorbing agents may be used in combination. Examples of the ultraviolet absorbing agent that may be used include benzophenone compounds, benzotriazole compounds, triazine compounds, azomethine compounds, indole compounds, dibenzoylresorcinol derivatives, benzodithiol compounds, and oxazolone compounds.

[0095] Examples of the benzophenone compounds include 2-hydroxy-4-(2-methacryloyloxyethoxy)benzophenone, 2-hydroxy-4-(4-methacryloyloxybutoxy)benzophenone, 2,2'-dihydroxy-4-(2-methacryloyloxyethoxy)benzophenone, 2,4-dihydroxy-4'-(2-methacryloyloxyethoxy)benzophenone, 2,2',4-trihydroxy-4'-(2-methacryloyloxyethoxy)benzophenone, 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, and 2-hydroxy-4-(3-methacryloyloxy-1-hydroxypropoxy)benzophenone.

[0096] Examples of the benzotriazole-based compound include 2-(2-hydroxy-5-methacryloyloxyphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methacryloyloxymethylphenyl)-2H-benzotriazole, 2-[2-hydroxy-5-(2-methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2-hydroxy-3-tert-butyl-5-(2-methacryloyloxyethyl)phenyl]-5-chloro-2H-benzotriazole, and 2-[2-hydroxy-3-methyl-5-(8-methacryloyloxyoctyl)phenyl]-2H-benzotriazole.

[0097] The triazine-based compound is, for example, 2-[4-(4,6-bis-biphenyl-4-yl-[1,3,5]triazin-2-yl)-3-hydroxy-phenoxy]-propionic acid 6-methyl-heptyl ester, 2-[4-(4,6-bis-{2-hydroxy-4-[1-(6-methyl-heptyloxycarbonyl)-ethoxy]-phenyl}-[1,3,5]triazin-2-yl)-3-hydroxy-phenoxy]-propionic acid 6-methyl-heptyl ester, reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenyl with oxirane, reaction product of 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine with (2-ethylhexyl)-glycidic acid ester.

[0098] Examples of the azomethine compounds include BONASORB UA-3701 (trade name, Orient Chemical Industry Co., Ltd.). Examples of the indole compounds include BONASORB UA-3911 (trade name, Orient Chemical Industry Co., Ltd.). Examples of the dibenzoylresorcinol derivatives include 4,6-dibenzoylresorcinol.

[0099] Examples of the benzodithiol compound include 2-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)-4,4-dimethyl-3-oxopentanitrile, 2-cyano-2-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)-2-ethylhexyl ester acetic acid, 2-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)propanedinitrile, 1,2-dibutyl-4-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)-3,5-pyrazolidinedione, 4-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)-3-(1,1-dimethyl ester)-5(4H)-isoxazolone, 4-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)-1,2-dibutyl phenyl-3,5-pyrazolidinedione, 2-(4,7-dihydroxy-5-methyl-1,3-benzodithiol-2-ylidene)propanedinitrile, 2,2'-(4,8-dihydroxybenzo[1,2-d:4,5-d']bis[1,3]dithiol-2,6-diylidene)bis[4,4-dimethyl-3-oxopentanenitrile], 2,2'-(4,8-dihydroxybenzo[1, 2-d:4,5-d']bis[1,3]dithiol-2,6-diylidene)bis[2-cyano-1,1'-bis(2-ethylhexyl)esteracetic acid], 4,4'-(4,8-dihydroxybenzo[1,2-d:4,5-d']bis[1,3]dithiol-2,6-diylidene)bis[2,4-dihydro-5-methyl-2-phenyl-3H-pyrazol-3-one], and the like.

[0100] Because of excellent compatibility with the curable transparent resin or transparent adhesive sheet, the ultraviolet absorber is preferably a benzotriazole-based compound and a benzophenone-based compound, and more preferably a benzotriazole-based compound. Commercially available benzotriazole-based compounds include, for example, Tinuvin 384-2, Tinuvin 326, Tinuvin 970, etc., manufactured by BASF, which are excellent in compatibility with the curable transparent resin. It should be noted that, for example, even if an ultraviolet absorber has low compatibility with a certain curable transparent resin, it can be modified and bonded to a part with high compatibility with the curable transparent resin matrix, thereby improving the compatibility of the ultraviolet absorber, and a wide range of ultraviolet absorbers can be used. That is, for example, a silicone-modified ultraviolet absorber can be suitably used for a silicone-based curable transparent resin.

[0101] <Resin film> The resin film 26 may be, for example, a PET film or a dielectric multilayer film formed by laminating a plurality of resin films having different refractive indices. The total thickness of the resin film 26 may be, for example, 25 μm to 200 μm. The resin film 26 may also have an infrared reflective film with a film thickness of about 100 nm to 500 nm on the surface. Examples of the infrared reflective film include a dielectric multilayer film, a liquid crystal alignment film, a coating containing an infrared reflective material, and a single-layer or multilayer infrared reflective film including a metal film.

[0102] <Light-adjusting materials and elements> The light control member 30 is an element capable of switching the light transmittance of the laminated glass 100 to 500. The light control member 30 is, for example, in a sheet shape. The thickness of the light control member 30 is, for example, 0.05 mm to 2.9 mm, preferably 0.05 mm to 2.0 mm, and more preferably 0.1 mm to 1.0 mm. The light control member 30 has a maximum dimension in the range of 300 mm to 3000 mm. Here, the "maximum dimension" means the longest dimension of the light control member 30 in a plan view of the first glass plate 11.

[0103] The light control element 78 is, for example, in the form of a sheet. The light control element 78 is located between a first base material 71 on which a first conductive layer 75 is formed, and a second base material 72 on which a second conductive layer 76 is formed.

[0104] The dimming element 78 is selected from the group consisting of, for example, a suspended particle device (SPD), a twisted nematic liquid crystal (TNLC), a polymer dispersed liquid crystal (PDLC), a polymer network liquid crystal (PNLC), a guest host liquid crystal (GHLC), a photochromic, an electrochromic, and an electrokinetic.

[0105] The effects of the present invention are particularly effective when the light control element 78 has at least one type selected from the group consisting of TNLC, PDLC, PNLC, and GHLC, which tend to cause color unevenness due to uneven distribution of liquid crystal. Also, the effects of the present invention are even more effective when the light control element 78 has GHLC, which is easily affected by even slight uneven distribution of liquid crystal because the inside of the light control element 78 is liquid.

[0106] The rotational viscosity (γ1) of the light control element 78 at 25° C. is preferably 2000 mPa·s or less. An example of the light control element 78 having a rotational viscosity (γ1) of 2000 mPa·s or less at 25° C. is GHLC. The rotational viscosity of the light control element 78 at 25° C. is more preferably 1000 mPa·s or less, further preferably 750 mPa·s or less, and particularly preferably 500 mPa·s or less. By setting the rotational viscosity (γ1) of the light control element 78 at 25° C. to 1000 mPa·s or less, the response speed can be made faster. By setting the rotational viscosity of the light control element 78 at 25° C. to 10 mPa·s or more, the light control member 30 and the laminated glass 100 to 500 can be more easily manufactured. The rotational viscosity can be measured using a parallel disk type rotational viscometer (B type viscometer).

[0107] In the portion of the laminated glass 100 to 500 having the light control member 30, the difference in visible light transmittance (Tv) between the dark state and the bright state is preferably 3% or more, more preferably 35% or more, even more preferably 50% or more, and particularly preferably 80% or more. Tv can be measured in accordance with JIS R 3212:2015.

[0108] <Base material> The first base material 71 is made of, for example, a transparent resin. The first base material 71 has at least one selected from the group consisting of, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyamide, polyether, polysulfone, polyethersulfone, polycarbonate (PC), polyarylate, polyetherimide, polyetheretherketone, polyimide, aramid, polybutylene terephthalate (PBT), triacetyl cellulose, polyurethane, and cycloolefin polymer.

[0109] The first base material 71 preferably has at least one selected from the group consisting of polyethylene terephthalate, polycarbonate, and cycloolefin polymer, and more preferably is made of any one of these.

[0110] The thickness of the first base material 71 is, for example, 5 μm to 500 μm, preferably 10 μm to 200 μm, and more preferably 50 μm to 150 μm.

[0111] The same can be said about the second base material 72 as about the first base material 71. Note that the second base material 72 may be made of a material different from that of the first base material 71. Also, the second base material 72 may have a thickness different from that of the first base material 71.

[0112] <Conductive layer> For example, a transparent conductive oxide (TCO) can be used for the first conductive layer 75. Examples of TCO include, but are not limited to, tin-doped indium oxide (ITO), aluminum-doped zinc oxide (AZO), and indium-doped cadmium oxide.

[0113] Transparent conductive polymers such as poly(3,4-ethylenedioxythiophene) (PEDOT) or poly(4,4-dioctylcyclopentadithiophene) can also be suitably used as the first conductive layer 75. Also suitably used as the first conductive layer 75 can be a laminated film of a metal layer and a dielectric layer, silver nanowires, and a metal mesh of silver or copper.

[0114] The first conductive layer 75 can be formed by using a physical vapor deposition (PVD) method such as a sputtering method, a vacuum deposition method, an ion plating method, etc. Alternatively, the first conductive layer 75 may be formed by using a chemical vapor deposition (CVD) method or a wet coating method.

[0115] The thickness of the first conductive layer 75 is not particularly limited, but may be, for example, in the range of 200 nm to 2 μm. The same can be said about the second conductive layer 76 as about the first conductive layer 75. However, the second conductive layer 76 may be composed of a different material from the first conductive layer 75. Furthermore, the second conductive layer 76 may have a different thickness from the first conductive layer 75.

[0116] <Power supply> As shown in Figs. 3, 4, 9, and 10, the power supply 50 is arranged at a position overlapping the light shielding portions 61 and 62 in a plan view. The power supply 50 is inserted between the first conductive layer 75 and the second conductive layer 76 and is electrically connected. The power supply 50 applies a voltage from an external device to the conductive layer. In the example of Fig. 1, the power supply 50 is located on the long side of the laminated glass 100, but the position of the power supply 50 is not limited thereto and may be any position, for example, on the short side. In addition, a plurality of power supply bodies 50 may be arranged, and they may be arranged on the same side, or may be arranged to face each other on opposing sides, or may be arranged on adjacent sides.

[0117] From the viewpoints of cost and availability, the power supply 50 can be preferably made of a flexible belt-shaped connection member such as a metal foil or metal wire covered with an insulating material, or an FPC (Flexible Printed Circuit). The metal foil or metal wire preferably contains, for example, gold, silver, or copper, and more preferably contains copper. Carbon may be used instead of these metals.

[0118] The power supply body 50 can be adhered to the first conductive layer 75 and the second conductive layer 76 of the light control component 30 by any of a conductive adhesive material (conductive adhesive layer), an anisotropic conductive film, solder, etc. The power supply body 50 may also be in direct contact with the first conductive layer 75 and the second conductive layer 76 without using a conductive adhesive material, an anisotropic conductive film, or solder.

[0119] The insulating member may be a thermosetting resin or a thermoplastic resin. For example, the insulating member may be a polyester resin such as PET, PEN, or PBT, a polyamide resin such as nylon 6, nylon 66, or nylon 610, a polyimide resin such as polyimide, polyamideimide, or polyetherimide, a fluorine resin, polyethersulfone, polyetherketone, polyethersulfide, polyarylate, polyesterether, wholly aromatic polyamide, polyaramid, polypropylene (PP), PC, or liquid crystal polymer. Among these, a polyimide resin such as polyimide is preferably used.

[0120] The thickness of the current collector 50 is preferably 0.05 mm to 0.4 mm. In order to ensure sufficient strength and prevent defects such as wire breakage, the thickness of the current collector 50 is preferably 0.05 mm or more, and more preferably 0.1 mm or more. In order to reduce the generation of air bubbles around the current collector 50, the thickness of the current collector 50 is preferably 0.4 mm or less.

[0121] <Sealing material> The sealing member 40 prevents the adhesive portion 20 from protruding from the periphery of the first glass plate 11 and the second glass plate 12 when the first glass plate 11 and the second glass plate 12 are adhered to each other. The sealing member 40 may be any curable transparent resin that can be used for the adhesive portion 20, but a photocurable transparent resin is preferable. In addition, since the sealing member 40 can be concealed by providing a light-shielding portion on at least one of the first glass plate 11 and the second glass plate 12, the sealing member 40 does not have to be transparent.

[0122] The shear modulus of elasticity of the seal member 40 at 25° C. is preferably equal to or greater than the shear modulus of elasticity of the adhesive portion 20 at 25° C. The shear modulus of elasticity can be measured under the conditions described above.

[0123] In a plan view of the first glass plate 11, the width of the seal member 40 may be 0.05 mm or more, preferably 0.1 mm or more, and more preferably 0.2 mm or more from the peripheral edge of the first glass plate 11. The width of the seal member 40 may be 10 mm or less.

[0124] (Method of manufacturing laminated glass according to one embodiment of the present invention) Next, an example of a method for producing a laminated glass according to an embodiment of the present invention will be described. Fig. 11 shows a schematic flow of the method for producing a laminated glass according to an embodiment of the present invention.

[0125] As shown in FIG. 11, a method for producing laminated glass according to one embodiment of the present invention includes the following steps: The method includes: (1) a forming step (step S100) of forming a sealing member on at least a portion of the peripheral edge of at least one of the first glass plate and the second glass plate in a plan view, and forming an adhesive section containing a curable transparent resin on at least one main surface of the first glass plate and the second glass plate; (2) a laminating step (step S200) of stacking the first glass plate, the adhesive section, and the second glass plate in this order to form a laminate in which the adhesive section contacts the first glass plate, the second glass plate, and the first main surface, the second main surface, and a side surface of the dimming component to which the power supply is connected; and (3) an adhesion step (step S300) of joining the first glass plate, the adhesive section, the second glass plate, and the sealing member to each other in the laminate.

[0126] Each step will be described below. The reference symbols shown in Figs. 1 to 10 will be used to represent each component.

[0127] Step S100 is a step of forming a seal member and an adhesive portion. The seal member 40 is formed on at least a part of the periphery of at least one of the first glass plate and the second glass plate in a plan view. The seal member 40 may have a curable transparent resin or an adhesive transparent sheet. When the seal member 40 has a curable transparent resin, the curable transparent resin before curing can be filled into a known discharge device such as a hand gun to form the seal member 40. Then, the curable transparent resin is cured by a curing method according to the type of the curable transparent resin. When the seal member 40 has an adhesive transparent sheet, a continuous frame-shaped adhesive transparent sheet can be prepared to form the seal member 40. In addition, the seal member 40 may be formed by combining a plurality of strip-shaped adhesive transparent sheets.

[0128] The seal member 40 can be formed directly on at least one of the main surfaces of the first and second glass plates. The term "formed directly on the main surfaces" includes the case where a light-shielding portion or various coatings are formed on the main surfaces of the glass plates as necessary, and the seal member 40 is formed on the light-shielding portion or various coatings. The seal member 40 can also be formed indirectly on at least one of the main surfaces of the first and second glass plates via an adhesive layer (e.g., the second adhesive layer 22, the third adhesive layer 23) that forms an adhesive portion, or a resin film 26, etc. However, the seal member 40 is formed before forming an adhesive layer having a curable transparent resin.

[0129] The adhesive portion 20 has a curable transparent resin and is formed directly on at least one of the main surfaces of the first glass plate and the second glass plate. When the adhesive portion 20 has a single adhesive layer (i.e., the first adhesive layer 21) having a curable transparent resin, the first adhesive layer 21 can be formed by filling a known discharge device such as a hand gun with uncured curable transparent resin and discharging only an amount that constitutes the adhesive portion 20 into the area surrounded by the seal member 40. The first adhesive layer 21 may be formed in stages. For example, the uncured curable transparent resin may be discharged in an amount smaller than the amount that constitutes the adhesive portion 20, the light control member 30 to which the power supply body 50 has been connected in advance may be left stationary, and then discharging may be resumed until the amount that constitutes the adhesive portion 20 is reached. In this case, the seal member 40 may also be formed in stages.

[0130] When the adhesive part 20 has a plurality of adhesive layers (for example, when the adhesive part 20 has a first adhesive layer 21, a second adhesive layer 22, and a third adhesive layer 23), the adhesive layers can be formed in any order. For example, a seal member 40 can be formed on the periphery of the first glass plate 11 (second glass plate 12), and then a curable transparent resin can be filled in the area surrounded by the seal member 40 to form the first adhesive layer 21 (second adhesive layer 22). In addition, a third adhesive layer 23 having an adhesive transparent sheet may be formed first on the second main surface of the light control member 30. Note that the adhesive layer having an adhesive transparent sheet can be a known adhesive transparent sheet adjusted to a desired size.

[0131] Step S200 is a lamination step for forming a laminate. The laminate is a structure in which a first glass plate 11, an adhesive portion 20, and a second glass plate 12 are laminated in this order. When the adhesive portion 20 is formed directly or indirectly on the main surface of one of the first glass plate 11 and the second glass plate 12, the other glass plate may be laminated on the adhesive portion 20. When the adhesive portion 20 is formed directly or indirectly partially on the main surfaces of both the first glass plate 11 and the second glass plate 12, the two glass plates may be laminated so that the partially formed adhesive portions are integrated with each other.

[0132] In either case, the laminate is formed so that the first main surface, the second main surface, and the side surface (i.e., all surfaces) of the light control component 30 are in contact with the adhesive part 20. Naturally, some pressure is applied to the light control component 30 during lamination, but lamination is possible without applying localized pressure that would cause the light control component 30 to deform and produce color unevenness. As a result, in the subsequent step S300 and thereafter, the adhesive part 20 is less likely to flow, and localized pressure that would deform the light control component 30 is less likely to be applied, reducing the occurrence of color unevenness. Step S200 may be performed under a reduced pressure atmosphere or under atmospheric pressure.

[0133] Step S300 is a bonding step of the constituent members of the laminate, and is specifically carried out by curing the curable transparent resin. Step S300 is carried out under milder conditions, with a lower temperature and pressure than the autoclave treatment in the manufacturing process of laminated glass having a thermoplastic interlayer, in order to reduce the occurrence of color unevenness. Step S300 may also be carried out under a reduced pressure atmosphere or atmospheric pressure. However, if air bubbles remain inside the laminate, the laminate may be heated and pressurized before or after the curing of the curable transparent resin to remove the air bubbles. In step S300, the absolute pressure applied to the adhesive part may be less than 0.5 MPa, and the temperature applied to the adhesive part may be less than 120°C.

[0134] When the curable transparent resin is a room temperature curing type, the laminate may be left to stand for a predetermined time. While the laminate is left to stand, the adhesive portion 20 is pressurized by at least the weight of the first glass plate 11, but may be pressurized at an absolute pressure of at least less than 0.5 MPa. The temperature during standing does not matter, but room temperature is preferable. When the curable transparent resin is a thermosetting type, it may be heated at a temperature lower than that of autoclave treatment. Specifically, the temperature may be less than 120°C, and if it is 115°C or less, it is preferable because it is easy to reduce the occurrence of color unevenness, more preferably 110°C or less, even more preferably 100°C or less, even more preferably less than 100°C, particularly preferably 90°C or less, and most preferably 80°C or less. When the curable transparent resin is a photocurable type, it is sufficient to irradiate a predetermined light that cures the curable transparent resin. The temperature does not matter, but room temperature is preferable.

[0135] [Example] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Laminated glass having the configurations shown in Examples 1 to 7 was produced as follows. Examples 1 to 6 are examples, and Example 7 is a comparative example.

[0136] (Example 1) Example 1 corresponds to the laminated glass 100 of the first embodiment. The first glass plate 11 and the second glass plate 12 were each made of soda lime glass that was rectangular, 300 mm long and wide, and 2 mm thick, and curved into a complex curve. The first glass plate 11 and the second glass plate 12 both had an ultraviolet transmittance of 75% at 380 nm. The seal member 40 was made of a heat-curable silicone-based curable transparent resin ("OP1912" manufactured by Momentive). The adhesive portion 20 (first adhesive layer 21) was made of a reaction-curable silicone-based curable transparent resin ("SN1001" manufactured by Momentive) (no ultraviolet absorber used). The light-control member 30 was made of a GHLC light-control film that was 80 mm long and wide and 0.4 mm thick. The following describes the steps for producing the laminated glass of Example 1, in which the convex surface of the first glass plate 11 and the concave surface of the second glass plate 12 face each other.

[0137] First, a seal member 40 having a width of 1 mm was provided on the periphery of the second glass plate 12. Then, heat of 40°C to 80°C was applied for 30 minutes to harden the thermosetting type permeable transparent resin constituting the seal member 40. Next, a certain amount of a mixture of agent A and agent B was discharged from a mixing nozzle onto the main surface of the second glass plate 12 to provide a predetermined thickness of a reactive hardening type hardening transparent resin to become the first adhesive layer 21. Then, a light control member 30 connected to a power supply body 50 was placed on the hardening transparent resin at the center position of the second glass plate 12 in a plan view.

[0138] Next, an uncured seal member was further provided on the cured seal member so that the power supply body 50 was sandwiched between the seal member 40, and the uncured seal member was cured at 40°C to 80°C. Then, the same reaction-curing type curable transparent resin was further filled on the light control member 30 and the power supply body 50, and the adhesive part 20 was formed so that the first main surface, the second main surface, and the side surface (i.e., all surfaces) of the light control member 30 were in contact with the curable transparent resin. Next, the first glass plate 11 was laminated so as to be in contact with the seal member 40 and the adhesive part 20, and the adhesive part 20 was left to stand in a state where it was pressed by the weight of the first glass plate 11 until the reaction-curing type curable transparent resin was cured. In this way, the laminated glass of Example 1 was obtained.

[0139] (Example 2) Example 2 corresponds to the laminated glass 100 of the first embodiment. Example 2 differs from Example 1 in that an ultraviolet absorber was added to the curable transparent resin, but other aspects are the same as those of the laminated glass of Example 1. Tinuvin 384-2 was used as the ultraviolet absorber. The ultraviolet absorber was dissolved in a mixture of agent A of a reactive curing type curable transparent resin (SN1001) and agent B by heating and stirring at 60°C.

[0140] (Example 3) Example 3 is an example corresponding to the laminated glass 100 of the first embodiment. Example 3 is different from Example 1 in that an ultraviolet absorbing agent is added to the curable transparent resin, and the rest is the same as the laminated glass of Example 1. As the ultraviolet absorbing agent, a silicone-modified compound was used, which was obtained by adding 1,2-dibutyl-4-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)-3,5-pyrazolidinedione to epoxy-modified silicone ("KF-105" manufactured by Shin-Etsu Chemical Co., Ltd.) and an amine catalyst, and heating and stirring at 80°C. That is, a silicone-modified ultraviolet absorbing agent was used. After dissolving the silicone-modified ultraviolet absorbing agent in the A agent of the reactive curing type silicone-based curable transparent resin (SN1001), the mixture of the B agent was heated and stirred at 60°C to dissolve it.

[0141] (Example 4) Example 4 is an example corresponding to the laminated glass 100 of the first embodiment. Example 4 differs from Example 1 in that an ultraviolet absorbing coating containing Tinuvin 384-2 as a main component is formed on the main surface of the second glass plate 12 facing the light control member 30, but other than that, Example 4 is the same as the laminated glass of Example 1. The ultraviolet absorbing coating was applied before the process of forming the seal member 40.

[0142] (Example 5) Example 5 corresponds to the laminated glass 400 of the fourth embodiment. The first adhesive layer 21 was made of the reaction-curing type curable transparent resin (without ultraviolet absorbing agent) whose preparation method was described above, and the second adhesive layer 22 was made of a 300 mm thick laminated glass having a length and width of 300 mm and a thickness of 50 mm. μ The difference from Example 1 is that a 1.2m acrylic transparent adhesive sheet (PDS1 manufactured by PANAC) was used; other materials are the same as in Example 1.

[0143] First, the second adhesive layer 22 and the light control member 30, in which the power supply body 50 is connected to the center of the second glass plate 12 in a plan view, were placed on the main surface of the second glass plate 12. Next, a seal member 40 having a width of 1 mm was provided on the periphery of the second adhesive layer 22. After that, the first adhesive layer 21 was placed so that the first main surface, the second main surface, and the side surface (i.e., all surfaces) of the light control member 30 were in contact with the curable transparent resin, and an adhesive portion 20 was formed. The subsequent steps were the same as those in Example 1. In this manner, the laminated glass of Example 5 was obtained.

[0144] (Example 6) Example 6 is an example corresponding to the laminated glass 400 of the fourth embodiment. Example 6 differs from Example 5 in that an acrylic transparent adhesive sheet containing a benzotriazole ultraviolet absorber (manufactured by Gunze Limited, "NNEA0M") was used as the second adhesive layer 22, but the rest is the same as the laminated glass of Example 5. The ultraviolet absorber was applied before the second adhesive layer 22 was disposed.

[0145] (Example 7) In Example 7, the sealing member 40 and the adhesive portion 20 were not used, and instead, two PVB intermediate films (manufactured by Eastman Chemical Co.) each having a length and width of 300 mm and a thickness of 0.76 mm were used. The other members were the same as in Example 1.

[0146] First, two PVB interlayers with a light control member 30 between them were laminated on the main surface of the second glass plate 12. At this time, the light control member 30 was disposed at the center of the second glass plate 12 in a plan view. The first glass plate 11 was further laminated so as to be in contact with the PVB interlayer to obtain a laminate. The obtained laminate was placed in a rubber bag, and the temperature in the rubber bag was controlled to 100°C to 140°C and the absolute pressure was controlled to 0.01 MPa to 0.1 MPa for primary pressure bonding. Thereafter, the laminated glass of Example 7 was obtained by further performing secondary pressure bonding in an autoclave, controlling the temperature to 120°C to 140°C and the absolute pressure to 0.5 MPa to 1.4 MPa.

[0147] The laminated glasses shown in Examples 1 to 7 were evaluated for color unevenness and weather resistance. The configuration of each laminated glass and the evaluation results are shown in Table 1.

[0148] [Evaluation of color unevenness] With the light-adjusting member 30 in a dark state, the laminated glass was visually observed from the first glass plate 11 side to evaluate color unevenness. When color unevenness was observed over the entire light-adjusting member 30, it was rated as "C," when color unevenness was observed in only a part of the light-adjusting member 30, it was rated as "B," and when color unevenness was not observed in the light-adjusting member 30, it was rated as "A."

[0149] [Evaluation of UV transmittance] Ultraviolet light with a wavelength of 380 nm was incident on one of the first glass plate 11 and the second glass plate 12 so as to pass through the light control component 30, and the transmittance of the ultraviolet light with a wavelength of 380 nm emitted from the other glass plate was measured.

[0150] [Weather resistance evaluation] Weather resistance evaluation was performed to evaluate the effect of deterioration of the light control component 30 due to ultraviolet rays. Using a xenon weather meter, the laminated glass was exposed to a black panel temperature of 83°C and an irradiation amount of 150 W for 1500 hours, and then the visible light transmittance (Tv) was measured in a dark state. Tv was measured using a Hitachi High-Tech UH4150, A light source, in accordance with JIS R 3212:2015. When the absolute value of the change in the visible light transmittance of the laminated glass before and after the test was 1.5% or less, it was rated as "AA", when it was 2.0% or less, it was rated as "A", and when it was more than 2.0% and 5.0% or less, it was rated as "B".

[0151] [Table 1] From Table 1, it can be seen that the occurrence of color unevenness is reduced in laminated glass having a light control component, since the adhesive part 20 has a curable transparent resin. It can also be seen that the weather resistance of laminated glass having a light control component is improved by including an ultraviolet absorber. In particular, the weather resistance was further improved by using a silicone-modified ultraviolet absorber. Furthermore, by including a second adhesive layer (acrylic transparent adhesive sheet) in addition to the first adhesive layer, the position of the light control component was less likely to shift relative to the glass substrate. [Explanation of symbols]

[0152] 100 Laminated Glass 11 First Glass Pane 12 Second Glass Pane 20 Adhesive part 21 First adhesive layer 22 Second adhesive layer 26 Resin Film 30 Light control components 40 Sealing material 50 Power feeder 60 Shading section 71 First substrate 72 Second substrate 75 First conductive layer 76 Second conductive layer 78 Light control element 79 Encapsulating materials G center of gravity S Gap

[0153] The entire contents of the specification, claims, drawings and abstract of Japanese Patent Application No. 2020-140208, filed on August 21, 2020, are hereby incorporated by reference as the disclosure of the specification of the present invention.

Claims

1. A first glass sheet; a second glass plate facing the first glass plate; A light control member having a power supply connected thereto, an adhesive portion, and a seal member are provided between the first glass plate and the second glass plate, the sealing member overlaps at least a portion of a peripheral edge of the first glass plate in a plan view, The adhesive portion is in contact with the first glass plate, the second glass plate, and a first main surface, a second main surface, and a side surface of the light control component, The adhesive portion of the laminated glass comprises a curable transparent resin.

2. The laminated glass according to claim 1 , wherein the seal member is in contact with at least one of the first glass sheet and the second glass sheet.

3. The adhesive portion has a first adhesive layer, the curable transparent resin of the adhesive portion is included in the first adhesive layer, The laminated glass according to claim 1 , wherein the first adhesive layer is in contact with each of the first glass plate, the sealing member, and the first main surface and the side surface of the light control member.

4. The laminated glass of claim 3 , wherein the first adhesive layer contacts the second glass sheet.

5. The laminated glass according to claim 3 or 4, wherein the first adhesive layer has a thickness of 1 μm or more and 1000 μm or less.

6. The first adhesive layer has a shear modulus of 1.0×10 at 25° C. 3 Pa or more 2.0×10 5 The laminated glass according to claim 3 , wherein the modulus of elasticity is 0.01 Pa or less.

7. The adhesive portion has a second adhesive layer, The second adhesive layer has a transparent adhesive sheet, The laminated glass according to claim 3 , wherein the second adhesive layer is in contact with each of the first adhesive layer, the second main surface of the light control component, and the second glass plate.

8. The adhesive portion has a second adhesive layer and a third adhesive layer, The second adhesive layer has a transparent adhesive sheet, A resin film is provided between the second adhesive layer and the third adhesive layer, the second adhesive layer is in contact with the resin film and the second glass plate; The laminated glass according to claim 3 , wherein the third adhesive layer is in contact with the resin film and a second main surface of the light control component.

9. The laminated glass according to claim 7 or 8, wherein the second adhesive layer is in contact with the sealing member.

10. The laminated glass according to claim 7 , wherein the second adhesive layer has a thickness of 1 μm or more and 1000 μm or less.

11. The second adhesive layer has a shear modulus of 1.0×10 at 25° C. 3 Pa or more 2.0×10 5 The laminated glass according to claim 7 , wherein the modulus of elasticity is 0.01 Pa or less.

12. The laminated glass according to claim 1 , wherein the adhesive portion comprises an ultraviolet absorbing agent.

13. 13. The laminated glass according to claim 12, wherein the ultraviolet absorber comprises at least one selected from the group consisting of benzophenone compounds, benzotriazole compounds, triazine compounds, azomethine compounds, indole compounds, dibenzoylresorcinol derivatives, benzodithiol compounds, and oxazolone compounds.

14. The laminated glass according to claim 12 or 13, wherein the ultraviolet absorber is an ultraviolet absorber having a moiety having high compatibility with the curable transparent resin bonded thereto.

15. The laminated glass according to any one of claims 12 to 14, wherein the curable transparent resin contains a silicone-based curable transparent resin, and the ultraviolet absorber contains a silicone-modified ultraviolet absorber.

16. The laminated glass according to any one of claims 12 to 15, wherein the adhesive joint has a transmittance of ultraviolet light having a wavelength of 380 nm of 0% or more and 20% or less.

17. 17. The laminated glass according to claim 1, wherein the first glass sheet and the second glass sheet both have a curved shape.

18. The laminated glass according to claim 1 , wherein the light control member has a light control element containing liquid crystal.

19. The laminated glass according to claim 18 , wherein the light control element has a rotational viscosity at 25° C. of 2000 mPa·s or less.

20. A first glass sheet; a second glass plate facing the first glass plate; A method for manufacturing laminated glass including a light control member having a power supply connected thereto, an adhesive portion, and a seal member, the method comprising the steps of: a forming step of forming the seal member on at least a part of a peripheral edge of at least one of the first glass plate and the second glass plate in a plan view, and forming the adhesive portion containing a curable transparent resin on a main surface of at least one of the first glass plate and the second glass plate; a lamination process in which the first glass plate, the adhesive portion, and the second glass plate are laminated in this order to form a laminate in which the adhesive portion contacts the first glass plate, the second glass plate, and a first main surface, a second main surface, and a side surface of the light control component to which the power supply body is connected; a bonding step of bonding the first glass plate, the adhesive portion, the second glass plate, and the seal member to one another in the laminate.

21. The method for producing laminated glass according to claim 20 , wherein in the bonding step, an absolute pressure applied to the bonded joint is less than 0.5 MPa and a temperature applied to the bonded joint is less than 120° C.

22. The method for producing laminated glass according to claim 21 , wherein in the bonding step, a temperature applied to the bonded joint is less than 100° C.

Citation Information

Patent Citations

  • JP1991012219U

  • Method for manufacturing liquid crystal cell, method for manufacturing dimming material, and method for manufacturing glass laminate

    JP2016164617A

  • Light reflection film, and optical film using the same, functional glass, and head-up display

    JP2017198981A

  • Glass laminate

    JP2019182738A

  • Light control device and manufacturing method therefor

    JP2020118903A